2D luminescent metal–organic framework: efficient and highly selective detection of 2, 4, 6-trinitrophenol at the ppb level. Issue 4 (24th December 2020) - Fan, Ming Yue; Fu, Peng; Li, Jiao; Su, Zhong Min; Li, Xiao; Pan, Qing Qing; Hu, Xiao Li
Abstract : A 2D Cd-MOF (CUST-531 ) was reported as a sensor to detect TNP with high sensitivity and selectivity. The quenching mechanism is the turn-off response of the fluorescence signal, which can be observed by the naked eye under UV-vis lamp irradiation. Abstract : A unique 2D metal–organic framework (MOF), formulated as [Cd(L )0.5 (H2 L1)·DMF] (CUST-531 ) (L : 9, 10-bis( N -benzimidazolyl)-anthracene; H2 L1: 5-aminoisophthalic acid), has been successfully prepared by a hybrid ligand strategy based on solvothermal synthesis conditions. CUST-531 was characterized by single X-ray diffraction, PXRD (powder X-ray diffraction), TGA (thermogravimetric analysis) and IR (infrared spectrophotometer). CUST-531 contains 1D chains based on binuclear Cd clusters, which are further connected to establish a 4-c 2D layered network by the bridging ligands L . The fluorescence sensing experiments show that the strong emission properties of CUST-531 could be used to sensitively and rapidly detect 2, 4, 6-trinitrophenol (TNP ) at the ppb level. The fluorescence quenching mechanisms have been systematically studied through theoretical analysis and experiments, which may be the cause of the turn-off of the fluorescence signal when CUST-531 detected TNP .